Perceptions on the lack of time for practice and course work among music students in UiTM / Mohamad Zharif Mohamad Zaki - Mohamad Zaki, Mohamad Zharif (2014)
This study is actually to investigate the lack of practice time on principal instrument and the lack of time on doing the course works among the music students in UiTM. It identified the relationship between the reasons on lack of practice time and lack of time on doing course works. Besides that, this study also helps the students to manage their time properly and dividing the time equally between practice time and course works. Hence, this study can also help to suggest the best way that can lessen the lack of practice time on principal instrument and lack of time on doing course works among music students in UiTM including Bachelor Degree in Music Performance, Bachelor Degree in Music Composition, Bachelor Degree in Music Education and also Diploma in Music.